TNX-1500, a crystallizable fragment–modified anti-CD154 antibody, prolongs nonhuman primate cardiac allograft survival - Miura, Shuhei; Habibabady, Zahra A.; Pollok, Franziska; Ma, Madelyn; Rosales, Ivy A.; Kinoshita, Kohei; Pratts, Shannon; McGrath, Gannon; Chaban, Ryan; Fogarty, Siobhan; Meibohm, Bernd; Daugherty, Bruce; et al. (American journal of transplantation, 2023)
Blockade of the CD40/CD154 T cell costimulation pathway is a promising approach to supplement or replace current clinical immunosuppression in solid organ transplantation. We evaluated the tolerability and activity of a novel humanized anti-CD154 monoclonal antibody, TNX-1500 (TNX), in a nonhuman primate heterotopic cardiac allogeneic (allo) transplant model. TNX-1500 contains a rupluzimab fragment antigen-binding region and an immunoglobin G4 crystallizable fragment region engineered to reduce binding to the crystallizable fragment gamma receptor IIa and associated risks of thrombosis. Recipients were treated for 6 months with standard-dose TNX (sTNX) monotherapy, low-dose TNX monotherapy (loTNX), or loTNX with mycophenolate mofetil (MMF) (loTNX + MMF). Results were compared with historical data using chimeric humanized 5c8 monotherapy dosed as for loTNX but discontinued at 3 months. Median survival time was similar for humanized 5c8 and both loTNX groups, but significantly longer with sTNX (>265 days) than with loTNX (99 days) or loTNX + MMF (88 days) (P < 0.05 for both comparisons against sTNX). Standard-dose TNX prevented antidonor alloantibody elaboration, inhibited chronic rejection, and was associated with a significantly reduced effector T cells/regulatory T cells ratio relative to loTNX with MMF. No thrombotic complications were observed. This study demonstrated that TNX was well tolerated, prolongs allograft survival, and prevents alloantibody production and cardiac allograft vasculopathy in a stringent preclinical nonhuman primate heart allotransplant model.